INCREASING THE EFFICIENCY OF THE PROCESS OF PREPARING PRESCHOOL STUDENTS FOR PEDAGOGICAL ACTIVITY IN HIGHER EDUCATION - Alimova Zulfiya Karimovna (American Journals, 2023)
In fact, there is talk about further improvement of the pre-school education system, ensuring that the educational process of the mature generation is properly implemented by educators, and effectively organizing the process of improving their qualifications.
Keywords: education, method, preschool education, curriculum